A method and apparatus for high intensity ultrasonic treatment Of baking materials. - Chin, Nyuk Ling; Tan, Mei Ching; Che Pa, Nasrul Fikry; Yusof, Yus Aniza (2010)

(untitled)
The present invention discloses a high intensity ultrasonic treatment method and apparatus that is used in conjuction with an existing commercial dough or batter mixer to enhance the rheological, aeration and textural properties of the dough or batter. This change in properties is a result of the phenomenon of acoustic cavitation induced in the dough or batter by treatment with high intensity ultrasonic waves. The present invention discloses a moxing bowl of an existing mixer system that is preloaded with dough or batter, the bowl is located at the center of an ultrasonic bath tank filled with a working fluid. The effect of ultrasonic waves with power levels above 1 kW can be observed over the entire or partial mixing period of the dough or batter. The ultrasonic waves of the present invention are generated by a plurality of ultrasonic wave generators (104A, 104B) and piezoelectric transducers mounted on a stainless steel tank. The electrical energy received in each transducer will be converted into appropriate mechanical expansion and contractions in the piezoelectric ceramics of the transducer thus leading to pressure waves being transmitted to the dough or batter to be mixed. The generation and transmission of high intensity ultrasonic waves to the dough or batter affects its rheological, aeration and textural properties.